1994
DOI: 10.1002/art.1780371018
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term iloprost infusion therapy for severe pulmonary hypertension in patients with connective tissue diseases

Abstract: Objective. To determine the effects of short-term, maximum-tolerated-dose and long-term, optimum-dose iloprost treatment of severe pulmonary hypertension associated with systemic sclerosis (SSc) and the primary antiphospholipid syndrome (APS).Methods. Three patients with SSc and 2 with APS who had failed to respond to oral vasodilator therapy for pulmonary hypertension were enrolled in a 32-week, open, prospective trial. Short-term infusion of maximumtolerated doses and continuous infusion of optimum doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…20 Similar in function to PGI 2 , it is a potent vasodilator of the pulmonary vascular bed13 and also inhibits platelet aggregation 18. It is a relatively more stable compound than PGI 2 12.…”
Section: Discussionmentioning
confidence: 99%
“…20 Similar in function to PGI 2 , it is a potent vasodilator of the pulmonary vascular bed13 and also inhibits platelet aggregation 18. It is a relatively more stable compound than PGI 2 12.…”
Section: Discussionmentioning
confidence: 99%
“…Имеются в литературе описания случаев «первичной» (нетромбоэмболической) легочной гипертензии при АФС [28,29]. Подобные случаи отмечены и нами у двух больных высокопозитив ных по аФЛ.…”
Section: Discussionunclassified
“…Treatment modalities for patients with primary or secondary chronic pulmonary hypertension include potent drugs that either vasodilate the pulmonary vascular bed [17], prevent platelet aggregation [18], have anticytokine effects [19], or have antileukocyte effects [20]. Previous studies in pulmonary hypertension have shown that activated platelets and leukocytes contributed to the pulmonary vascular remodeling and chronic pulmonary hypertension [11, 12, 13].…”
Section: Discussionmentioning
confidence: 99%